Cyclic cryotherapy with vitamin D facilitates early rehabilitation after total knee arthroplasty - Li, Fulin; Mo, Yingrong; Huang, Xiao; Sun, Ke; Li, Baichuan; Yin, Dong (Frontiers in Medicine, 2024)
Objective This study aimed to evaluate the efficacy of cyclic cryotherapy and vitamin D administration on early rehabilitation after total knee arthroplasty (TKA), as its efficacy remains unclear. Methods We divided 150 patients (three groups) who underwent TKA into those treated with or without cyclic cryotherapy and vitamin D. Results Compared with patients who did not receive cyclic cryotherapy, those who received postoperative cyclic cryotherapy and vitamin D supplementation had significantly higher American Knee Society Scores (AKSS) on postoperative day (POD) 7 and at 1 month postoperatively; higher visual analogue scale (VAS) values on POD1–3 and POD7; reduced thigh swelling on POD3 and POD7; increased range of motion (ROM) on POD3, POD7, and at 1 month postoperatively; and reduced postoperative length of stay (PLOS). However, no significant difference in patient satisfaction was observed between the patient groups. At 1 and 3 months postoperatively, patients administered cyclic cryotherapy and vitamin D had significantly higher AKSS, ROM, and vitamin D levels than those who did not receive vitamin D. No perioperative complications such as surgical site infection, skin frostbite, or vitamin D intoxication were observed. Conclusion Cyclic cryotherapy post-TKA had short-term advantages in terms of AKSS, VAS, thigh swelling, ROM, PLOS, and accelerated rehabilitation, but did not improve patient satisfaction. Cyclic cryotherapy combined with vitamin D improved AKSS and ROM at 1 and 3 months postoperatively.